On Literary Criticism: Looking into Noerâs Moths from the planes of light of New Critics, Russian Formalists and the Structuralists - Herujiyanto, Herujiyanto (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2014)
Without denying the truth of the so-called silent enim leges inter arma [Law stands mute in the midst of arms], this paper makes use of the analytical perspectives of New Criticism, Russian Formalism and Structuralism to look into Arifin C. Noerâs play named Moths. It is admitted that literary critics often define their assumptions about literary work and the better way to go about reading it (and writing about it). The New Critics, Russian Formalists and the Structuralists are only three of them. According to Ian Ousby, the three groups can be described as formalists; they share a common conception: a work is autotelic, that is, complete in itself, written for its own sake, and unified by its form â that which makes it a work of art.1 Looking closer at the three movements, we would undoubtedly find that they are not exactly the same. The New Critics, for example, explicitly repudiated English Romanticism and its radical tradition while Russian Formalists merely attacked the utilitarian and social tradition.2 Then, Russian Formalists were concerned with the way in which the individual work of art was perceived differently against the background of the literary system as a whole. The Structuralists, however, set themselves the task of describing the organization of the total sign-system itself by dissolving the individual unit back into the langue of which it is a partial articulation.3 The end goal of this study is, thus, to find the possible ways to go about reading the play; to see how the playwright seems to write about his work; and to have a better understanding of the nature of the play.Â DOI: https://doi.org/10.24071/llt.2014.170106